Bhartiya Janta Party peripheri to centre - Bhambhri, C P (Delhi Shipra, 2001)
This is a study of how the Bhartiya Janta Party has occupied centre stage in India and what the reasons are for the shiftin Indian Society polity and economy.all those interested in Indian polity,research scholars and students of political science should
Keywords: Bhartiya Janta Party (India); India-Politics and government; Political parties-India